Foreign Policy-making, Immorality, Public Opinion, Russia-Ukraine War and a Looming 3rd World War: Challenges, Prospects and Stakes for International Relations and Human Security - SAKWE MASUMBE, Peter (Advances in Social Sciences Research Journal, 2022)
The Russia-Ukraine war would hardly shirk the philosophy that, historically, wars are created and fought but hardly have they ended without meaningful, multilateral and multifaceted diplomatic shuttling in roundtable conferences and dialogues between belligerents and their sympathisers. Usually, the aftermaths are the unavoidable humiliation or gallantry gives and takes in irreparable damages of human and material resources. In the Russia-Ukraine war, given the politics, amorality and public opinion orchestrated by Western media with incessant calls for NATO to declare a No Fly Zone over Ukraine, and informed by the Rational Actor Model, which assumes that, the main actor in foreign policymaking is a rational individual or group of individuals, who can make informed, calculated decisions that maximise value and perceived benefits to the state, (Allison, 1971, Zerbe 2021), and using the historical research methodology, this paper examines the challenges, prospects and stakes for international relations and humanity, in terms of the global insecurity intrinsic in the Russian-Ukraine War. Consequently, it advocates the international community’s refraining and dissuasion of escalation of a looming 3rd World War.